Gastric epithelial attachment of Helicobacter pylori induces EphA2 and NMHC‐IIA receptors for Epstein‐Barr virus. Issue 11 (13th September 2021) - Fekadu, Sintayehu; Kanehiro, Yuichi; Kartika, Andy Visi; Hamada, Kazuki; Sakurai, Nozomi; Mizote, Tomoko; Akada, Junko; Yamaoka, Yoshio; Iizasa, Hisashi; Yoshiyama, Hironori
Abstract: Epstein‐Barr virus (EBV)‐associated gastric cancer belongs to 1 of the 4 subtypes of gastric cancer and accounts for 10% of total gastric cancers. However, most cases of gastric cancer have a history of Helicobacter pylori infection. Therefore, we investigated the possibility that H. pylori infection promotes the development of EBV‐associated gastric cancer. H. pylori was exposed to principal EBV receptor, CD21, negative gastric epithelial cells, and then infected with EBV recombinant expressing enhanced green fluorescent protein. Changes in EBV infectivity due to prior H. pylori exposure were analyzed using flow cytometry. The treatment of gastric epithelial cells with H. pylori increased the efficiency of EBV infection. An increase was also observed when CagA‐deficient, VacA‐deficient, and FlaA‐deficient H. pylori strains were used, but not when cag pathogenicity island‐deficient H. pylori was used. The treatment of epithelial cells with H. pylori induced the expression of accessory EBV receptors, EphA2 and NMHC‐IIA, and increased the efficiency of EBV infection depending on their expression levels. When gastric epithelial cells were treated with EPHA2 or NMHC‐IIA siRNA, EBV infection via H. pylori attachment was decreased. The adhesion of H. pylori induced the expression of accessory EBV receptors in gastric epithelial cells and increased the efficiency of EBV infection. Abstract : We investigated the possibility that H. pylori infection promotes the development of EBV‐associated gastric cancer (EBVaGC). H. pylori adheres to gastric epithelial cells and induces low‐affinity EBV receptor expression in epithelial cells. A continuous increase in the number of EBV‐infected cells is expected during life‐long gastric inflammation caused by H. pylori . Therefore, H. pylori infection is thought to increase the incidence of EBVaGC by increasing the efficiency of EBV infection.